Chemical Composition, Chemometric Analysis, and Sensory Profile of Santolina chamaecyparissus L. (Asteraceae) Essential Oil: Insights from a Case Study in Serbia and Literature-Based Review - Biljana Lončar; Mirjana Cvetković; Milica Rat; Jovana Stanković Jeremić; Jelena Filipović; Lato Pezo; Milica Aćimović (Separations)
The flowers of Santolina chamaecyparissus have a distinct aroma and taste, with a wide range of applications in medicine, food, and packaging. Its essential oil offers numerous health benefits, including antioxidant, hepatoprotective, anticancer, antidiabetic, spasmolytic, anti-inflammatory, immunomodulatory, antimicrobial, and antiparasitic properties. Additionally, it is used as a flavoring agent in food and beverages and as a natural preservative in edible coatings for food packaging. This study investigates the chemical composition and sensory properties of the S. chamaecyparissus essential oil from Serbia, obtained via hydrodistillation, and includes a literature-based analysis of the existing profiles. Gas Chromatography–Mass Spectrometry (GC–MS) was employed for identifying the essential oil composition, while chemometric techniques like the genetic algorithm (GA), quantitative structure–retention relationship (QSRR) analysis, artificial neural network (ANN), and molecular descriptors were applied to ensure accurate and reliable results for authenticating the oil. Among the 47 identified compounds, oxygenated monoterpenes, especially artemisia ketone (36.11%), and oxygenated sesquiterpenes, notably vulgarone B (22.13%), were the primary constituents. Chemometric analysis proved effective in predicting the oil’s composition, and sensory evaluation revealed a herbal aroma with earthy, woody, and camphoraceous notes. A literature review highlighted the variability in oil composition due to geographical, environmental, and extraction factors, underscoring its chemical diversity, bioactivity, and potential applications.